2015
DOI: 10.1155/2015/527395
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Humoral Immunity toMycobacterium tuberculosis-Specific Antigens for Correlation with Clinical Status and Effective Vaccine Development

Abstract: Although tuberculosis remains a major global health problem, Bacille Calmette-Guérin (BCG) is the only available vaccine. However, BCG has limited applications, and a more effective vaccine is needed. Cellular mediated immunity (CMI) is thought to be the most important immune response for protection against Mycobacterium tuberculosis (Mtb). However, the recent failure of a clinical trial for a booster BCG vaccine and increasing evidence of antibody-mediated immunity prompted us to evaluate humoral immunity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 60 publications
2
33
1
1
Order By: Relevance
“…IgA against HrpA associated with improved severity markers on presentation in active TB disease [40]…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…IgA against HrpA associated with improved severity markers on presentation in active TB disease [40]…”
Section: Figurementioning
confidence: 99%
“…The presence of IgG against Ag85A has elsewhere been associated with decreased cavitation and a greater chance of sputum clearance of M.tb in a cohort of Mexican patients [38] The development of clinically defined AIDS is associated with waning antibody titres against M.tb antigens in purified protein derivative (PPD) – suggesting that the risk for severe disease in this population may not be exclusively due to loss of CD4 + cells [39]. IgA against α–crystallin (Acr) and HrpA are associated with improved markers of disease severity at the time of admission, with lower albumin and CRP levels seen in patients with higher titres of antibodies against these antigens [40]. These findings suggest that a vaccine eliciting such antibodies may prevent extrapulmonary TB and thus reduce mortality and morbidity from TB.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of antigen and adjuvant molecules can influence antigen-stimulated T cell cytokine profiles (11). Studies have demonstrated an inverse correlation between Th1-type hypersensitivity to M. tuberculosis and atopy in Japanese school children, and heat-killed or live Mycobacteria down-regulate Th2 responses to allergens (12,13). Consistent with this finding, another study has investigated using preparations of non-pathogenic M. vaccae in prophylactic treatment of allergic inflammation and asthma in murine models (14).…”
Section: Discussionmentioning
confidence: 89%
“…While IgA-HrpA levels correlated signi cantly with active TB, the IgA-16 kDa/ESAT6 was signi cantly associated with the nutritional status of the participants. Others reported IgA anti-mycobacterial antigens HrpA and MDP1 higher response among controls than in TB patients suggesting that different stress on bacterium and host modulates proteomic expression, and the IgA immune response may be protective [31]. Williams et al (2004) reported IgA against the 16 kDa α-cristalin mediated some protection against TB, as evidenced by reduced mycobacterial burden in the lungs [32].…”
Section: Discussionmentioning
confidence: 99%